Detecting familial hypercholesterolemia: An observational study leveraging mandatory universal pediatric total cholesterol screening in Slovakia - Raslova, Katarina; Donicova, Viera; Gonova, Katarina; Klabnik, Alexander; Tichy, Lukas; Bridges, Ian; Buckova, Dagmar; Zachlederova, Marie; Freiberger, Tomas; Vohnout, Branislav (Journal of clinical lipidology, 2024)
BACKGROUND: In Slovakia, a mandatory national universal pediatric total cholesterol (TC) screening program is in place to identify cases of familial hypercholesterolemia (FH). However, the program's effectiveness has not been systematically assessed. OBJECTIVE: This study aimed to estimate the prevalence of FH among parents of children that had elevated TC levels identified during screening. METHODS: This prospective, non-interventional, observational study enrolled parents of 11-year-old children who underwent TC screening in 23 selected pediatric outpatient clinics between 2017 and 2018. FH was diagnosed using the Dutch Lipid Clinic Network (DLCN) criteria and targeted next-generation sequencing. The primary objective was to estimate the proportion of children with a TC level of >188 mg/dL (>4.85 mmol/L) who had a parent with a confirmed diagnosis of FH. RESULTS: A total of 112 parents of 56 children with an elevated TC level were enrolled. Five children (8.9%) had a parent in whom FH was genetically confirmed. Without genetic analysis, all five parents would only be diagnosed with "possible FH" by DLCN criteria. Of parents, 83.9% (n = 94/112) had an low-density lipoprotein cholesterol (LDL-C) level of >116 mg/dL (>3 mmol/L), but only 5.3% (n = 5/94) received lipid-lowering therapy. Among the five parents with genetically confirmed FH, all had an LDL-C level >116 mg/dL (>3 mmol/L), with a mean (±SD) of 191 (±24) mg/dL (4.94 [±0.61] mmol/L). Only two of these parents received lipid-lowering therapy. CONCLUSIONS: The present study demonstrates the significance of mandatory universal pediatric TC screening in identifying families with FH and other at-risk families in need of lipid-lowering therapy.
Keywords: Cholesterol, LDL; Parents; hyperlipoproteinemie typ II; mužské pohlaví; Prospective Studies; Adult; Cholesterol; dítě; Child; Slovakia; Mass Screening; Slovenská republika; ženské pohlaví; Humans; prospektivní studie; Hyperlipoproteinemia Type II; LDL-cholesterol; dospělí; Female; plošný screening; rodiče; lidé; Male; cholesterol